Poverty and the impact of microcredit : a theological reflection on financial sustainability in Lusaka rural, Zambia - Phiri, Justin (Stellenbosch : Stellenbosch University, 2011)
Thesis (MTh (Practical Theology and Missiology))--University of Stellenbosch, 2011.